Inferring Diversity and Evolution in Fish by Means of Integrative Molecular Cytogenetics - Roberto Ferreira Artoni; Jonathan Pena Castro; Uedson Pereira Jacobina; Paulo Augusto Lima-Filho; Gideão Wagner Werneck Félix da Costa; Wagner Franco Molina (The Scientific World Journal)
Fish constitute a paraphyletic and profusely diversified group that has historically puzzled ichthyologists. Hard efforts are necessary to better understand this group, due to its extensive diversity. New species are often identified and it leads to questions about their phylogenetic aspects. Cytogenetics is becoming an important biodiversity-detection tool also used to measure biodiversity evolutionary aspects. Molecular cytogenetics by fluorescence in situ hybridization (FISH) allowed integrating quantitative and qualitative data from DNA sequences and their physical location in chromosomes and genomes. Although there is no intention on presenting a broader review, the current study presents some evidences on the need of integrating molecular cytogenetic data to other evolutionary biology tools to more precisely infer cryptic species detection, population structuring in marine environments, intra- and interspecific karyoevolutionary aspects of freshwater groups, evolutionary dynamics of marine fish chromosomes, and the origin and differentiation of sexual and B chromosomes. The new cytogenetic field, called cytogenomics, is spreading due to its capacity to give resolute answers to countless questions that cannot be answered by traditional methodologies. Indeed, the association between chromosomal markers and DNA sequencing as well as between biological diversity analysis methodologies and phylogenetics triggers the will to search for answers about fish evolutionary, taxonomic, and structural features.